2011
DOI: 10.1111/j.1600-6143.2010.03423.x
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal Villous Atrophy: A Cause of Chronic Diarrhea After Solid-Organ Transplantation

Abstract: † These two authors equally participated to this work.Persistent diarrhea is commonly observed after solid organ transplantation (SOT). A few cases of mycophenolate mofetil (MMF)-induced duodenal villous atrophy (DVA) have been previously reported in kidneytransplant patients with chronic diarrhea. Herein, we report on the incidence and characteristics of DVA in SOT patients with chronic diarrhea. One hundred thirty-two SOT patients with chronic diarrhea underwent an oesophago-gastroduodenoscopy (OGD) and a du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(39 citation statements)
references
References 42 publications
(83 reference statements)
0
38
1
Order By: Relevance
“…A recent study on DVA in SOT patients concluded that a main cause of DVA (24.6%) can be secondary to mycophenolate mofetil therapy. 2 In our study, mycophenolate mofetil was administered to 54 patients (51.9%), azathioprine to 50 patients (48.1%), tacrolimus to 40 patients (38%), and cyclosporine to 38 patients (36.5%) who developed DVA after transplant. The difference in immunosuppressive regimens can be due to the versatility of organs transplanted.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…A recent study on DVA in SOT patients concluded that a main cause of DVA (24.6%) can be secondary to mycophenolate mofetil therapy. 2 In our study, mycophenolate mofetil was administered to 54 patients (51.9%), azathioprine to 50 patients (48.1%), tacrolimus to 40 patients (38%), and cyclosporine to 38 patients (36.5%) who developed DVA after transplant. The difference in immunosuppressive regimens can be due to the versatility of organs transplanted.…”
Section: Discussionmentioning
confidence: 83%
“…[1][2][3][4] Posttransplant diarrhea not only leads to weight loss, dehydration, deranged serum creatinine, and inconsistent immunosuppressive drug levels, it also enhances the risk of graft loss and patient death. 1,[5][6][7][8] In our analyses of baseline characteristics, sex distribution in our study group was different from a previous study in which female sex and diabetes emerged as independent risk factors for diarrhea.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations